2015
DOI: 10.1073/pnas.1422504112
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and functional characterization of a neomorphic PTEN mutation

Abstract: Although a variety of genetic alterations have been found across cancer types, the identification and functional characterization of candidate driver genetic lesions in an individual patient and their translation into clinically actionable strategies remain major hurdles. Here, we use whole genome sequencing of a prostate cancer tumor, computational analyses, and experimental validation to identify and predict novel oncogenic activity arising from a point mutation in the phosphatase and tensin homolog (PTEN) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 35 publications
1
49
0
2
Order By: Relevance
“…It was predicted by online bioinformatics analysis that miR-17 may be involved in the regulation of PTEN gene expression. Previous results indicated that the PTEN gene is closely related to the proliferation, apoptosis, invasion and metastasis of cells (30). Therefore, it was speculated that the upregulation of miR-17 in AM endometrial cells resulted in the downregulation of PTEN, thus influencing the biological properties of endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was predicted by online bioinformatics analysis that miR-17 may be involved in the regulation of PTEN gene expression. Previous results indicated that the PTEN gene is closely related to the proliferation, apoptosis, invasion and metastasis of cells (30). Therefore, it was speculated that the upregulation of miR-17 in AM endometrial cells resulted in the downregulation of PTEN, thus influencing the biological properties of endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…7) and 2 individuals in The PTEN missense variant is within a highly conserved catalytic domain, and it is reported to give rise to completely inactive protein. 26,27 The…”
Section: Pathogenic Variants In Known Crc Susceptibility Genesmentioning
confidence: 99%
“…PTEN loss results in continuous activation of Akt signaling, which is correlated with the shorter overall survival of BRAF V 600E mutated melanoma patients (Bucheit et al, 2014). However, using whole-genome sequencing, Costa et al (2015) identified a novel point mutation (A126G) in the PTEN protein. They found that unlike canonical loss-of-function mutants, A126G mutation could produce an enzymatic gain-of-function in PTEN, activating the Akt signaling pathway and prompting cell proliferation in prostate cancer (Costa et al, 2015).…”
Section: Akt Signaling As a Target Of Tigmentioning
confidence: 99%
“…However, using whole-genome sequencing, Costa et al (2015) identified a novel point mutation (A126G) in the PTEN protein. They found that unlike canonical loss-of-function mutants, A126G mutation could produce an enzymatic gain-of-function in PTEN, activating the Akt signaling pathway and prompting cell proliferation in prostate cancer (Costa et al, 2015). These findings suggest the crucial role of the PTEN mutation in the Akt pathway in cancer.…”
Section: Akt Signaling As a Target Of Tigmentioning
confidence: 99%